Probabilistic conflict risk model for marine traffic within a sea port - Zhu, Jian Qin. (2008)
The conflict here includes collisions and near misses. By analyzing the marine vessel speed distribution and separation requirement between vessels, estimations of conflict risk in a general channel and at an intersection is obtained by combining the distributions of vessel arrivals. The basic idea of the model is that a conflict occurs when the distance between two vessels is less than the minimum separation requirement. The probabilistic conflict risk is the probability of conflict occurrence. The density function of location of vessels can be obtained by analyzing speed and time interval between vessels. Then the probabilistic conflict risk can be estimated by comparing the vessel locations with the minimum separation requirement.